A Prospective Study of Gunshot Injuries among the Patients Admitted to the Emergency Department (Indian Journal of Forensic Medicine & Toxicology, 2024)
Background-Increased incidence of firearm injuries in developing countries has been attributed to poverty, unemployment, political instability, lack of education and unequal distribution of wealth. Itis one of the important causes of morbidity and mortality in our country.Material and methods-This prospective study was conducted at Jawaharlal Nehru Medical College Hospital, AMU, Aligarh in the department of Forensic Medicine and in the Trauma and Emergency department between October 2018 to September 2020.130 patients of Gunshot injuries were included after obtaining informed consent.Results-Males (n=115; 88.46 %) were the predominant victims of gunshot injuries while female patients comprise of 11.54 % (n=15) only. Male to female ratio was 7.67:1. Majority (n=115; 88.46 %) of the gunshot injury cases were the result of homicidal motive. Lower (n=50; 35.46 %) and upper extremities (n=41; 31.53 %) were the most common sites of injury.Conclusion-There is a need to decrease the number of firearms used and sold in India. We need to eradicate illicit local community gun manufacturing units.
Keywords: Gunshot, Country made Guns, Illegal Weapons.